Tren Penggunaan TikTok Pada Kalangan Remaja Mahasiswa Jurusan Sosiologi Angkatan 2021 FISIP UPR - Anisa Pebrianti (Journal SOSIOLOGI, 2021)
The high need for using Internet-based on gadgets causes teenagers to spend most of their time accessing social media. At this time the TikTok application is one of the social media trends that is often accessed by all ages, including teenagers. This also happens to teenagers who are students of the Sociology department of FISIP UPR Batch of 2021. Researchers want to know the reasons why teenagers follow the trend to use the TikTok application. This research is descriptive quantitative research with student respondents as many as 64 people. Descriptive quantitative approach which aims to describe and explain can explain the data resulting from the questionnaire so as to obtain facts in the field. The data collection method used is data collection using observation and surveys. Data retrieval using a questionnaire distributed to students who download and access the TikTok application on their gadgets. Data analysis used thematic analysis. The conclusion of this study is that the use of the TikTok is for entertainment because TikTok can display various creator content videos that are considered interesting, charged with information according to their needs.